2004
DOI: 10.1186/gb-2004-5-2-r12
|View full text |Cite
|
Sign up to set email alerts
|

Versatile and open software for comparing large genomes

Abstract: The newest version of MUMmer easily handles comparisons of large eukaryotic genomes at varying evolutionary distances, as demonstrated by applications to multiple genomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
2,920
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 4,877 publications
(3,037 citation statements)
references
References 34 publications
5
2,920
1
4
Order By: Relevance
“…These gaps account for 2.9 Mb, or 0.1%, of the genome. By aligning the RefSeq assembly to PICR using MUMmer3.0 [Kurtz et al, 2004], we identified missing sequence for 125,812 (76%) of the RefSeq gaps (Figure 3.b and Methods). Sequence for a subset of RefSeq gaps was not identified in the PICR metassembly.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These gaps account for 2.9 Mb, or 0.1%, of the genome. By aligning the RefSeq assembly to PICR using MUMmer3.0 [Kurtz et al, 2004], we identified missing sequence for 125,812 (76%) of the RefSeq gaps (Figure 3.b and Methods). Sequence for a subset of RefSeq gaps was not identified in the PICR metassembly.…”
Section: Resultsmentioning
confidence: 99%
“…For each metassembly, one assembly is selected as the primary assembly. The scaffolds of a second assembly are subsequently mapped to the primary scaffolds using NUCmer [Kurtz et al, 2004]. A CE-statistic, based on the distance of mate-pair reads, is computed for both assemblies.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations